Self-Compassion terhadap Loneliness pada Dewasa Awal Kecenderungan Introvert - Auztry Deanti Rahayu; Popi Avati (Merpsy Journal, 2026)
This study aimed to examine the effect of self-compassion on loneliness among early adults with introverted tendencies in DKI Jakarta. The study employed a quantitative approach with a survey design involving 79 respondents aged 18–30 years, selected using purposive sampling. Research instruments included the UCLA Loneliness Scale Version 3, the Self-Compassion Scale (SCS), and the Big Five Inventory (BFI-10) as a screening tool for introverted personality tendencies. Data were analyzed using simple linear regression with the assistance of SPSS. The results indicated that self-compassion had a significant negative effect on loneliness (p < 0.05), with a contribution of 49.2%, suggesting that higher levels of self-compassion are associated with lower levels of loneliness. These findings are consistent with Cognitive Discrepancy Theory, which explains that loneliness is influenced by how individuals interpret discrepancies between expectations and the reality of social relationships. The study highlights the importance of developing self-compassion as a psychological protective factor in reducing loneliness among early adults with introverted tendencies.